Quality of use' in flipped classroom for entrepreneurship education: An instructor perspective - Nasirun, Noraini; Muhammad Noor, Sarina (2017)
Purpose - The emergence of technology in ICT gives a huge impact to teaching and learning activities. The integration of ICT in education creates multi-modalities in learning and teaching approach such as blended learning using flipped classroom. According to Graham et al. (2013), the growth of adoption in blended learning will lead to the need of revising the strategy, structure, as well as support to strengthen the quality of learning and teaching in the universities.Therefore, issues such as research methodology (Ahmad & Buchanan, 2015; Arbaugh, 2014; Zainuddin, Kamaluddin, & Hassan, 2012), research design and data analysis(Arbaugh & Hwang, 2012; Halverson, Graham, Spring, Drysdale, & Henrie, 2014) in blended learning must be addressed.Nigel Bevan (1995b) in his article ‘Measuring usability as quality of use’ explained that the quality was not solely about product but also in the context of use that involve interactions of users, task and environment in the application.The result of these experiences was referred to as the quality of use. Bevan further clarifies that ‘… quality of use can be used to measure usability as the extent to which specified goals can be achieved with effectiveness, efficiency and satisfaction by specified users carrying out specified tasks in specified environments’(Bevan, 1995a) Blended learning has been widely adopted by higher learning institutions (Graham et al., 2013). Arbaugh (2014), posited that flipped classroom can be utilized as a classroom setting for blended learning research. Chen, Wang, and Chen (2014) define flipped classroom as the condition where students will learn using several technologies at their own pace and complete the exercise in the physical class (Chen et al., 2014).Scholars found that flipped classroom has been used in various levels of educations such as K-12, undergraduates and postgraduate levels (Bristol, 2014; Butgereit & Osman, 2014; Horn & Staker, 2011).There are little studies that focus on blended learning for the business and management discipline, particularly the entrepreneurship education.This finding confirmed the arguments made by previous scholars that little studies of blended learning were conducted in entrepreneurship education (Arbaugh, 2010; Arbaugh & Hwang, 2015).However, the review of entrepreneurship education in Malaysia highlighted that course design is one important issues that need to be considered if institutions decided to blend the teaching and learning activities for this subject (Ahmad & Buchanan, 2015; Yusoff et al., 2014).The course design must be aligned with the current trends and objectives of entrepreneurship education of the institutions (Ahmad & Buchanan, 2015).In Universiti Teknologi MARA (UiTM), entrepreneuship education has also been taught as a formal subject at all levels of studies in UiTM (diploma, undergraduates, and graduates) (Loh et al., 2015).Students must enroll entreprenuership subject as one of the requirement for graduation.Importantly, the field of entrepreneuship should have a good partnership between business dicipline and other diciplines such as science and technology disciplines in order to improve the employability of graduates after completion of their study (Idris, 2011).In UiTM Perlis Branch, the entrepreneurship subject (Fundamentals of Entrepreneurship – ENT300) for diploma students has leverage the flipped classroom since 2012 because of problems related with high enrollmentin this subject (up to 1,400 students per semester) and limited instructors (10 instructors) who can teach the subject.The continuous assessments related with a project (business plan), presentation and mid-semester examination. Since the implementation of the flipped classroom for ENT300, it improves the student performance tremendously, submission project on time (Week 10), one-day presentation (Week 11), and half a day mid-semester examination (Week 13).Hence, this paper aim to identify the ‘quality of use’ in flipped classroom for entrepreneurship education from instructor point of view related with the matter.This article highlight the finding of a pilot interview for a qualitative study. Since this study focused on user experience, therefore ‘quality of use’ has been operationalized as the extent a flipped classroom fulfills the needs fundamentals of Entrepreneurship students for a particular semester.